Laparoscopic Surgery for Seminal Vesicle Cysts and Ureterocele with Urination Disorder: A Case Report of Zinner Syndrome - Maehana, Takeshi (J Endourol Case Rep, 2018)
Background: Zinner syndrome is defined as seminal vesicle cysts with ipsilateral renal agenesis and an ectopic ureter. Symptomatic cases are very rare. In this article, we present a laparoscopic approach for a case of Zinner syndrome. Case Presentation: The patient was a 21-year-old male with difficult urination. A right seminal vesicle cyst and right kidney agenesis associated with ureterocele were found on examination and he was diagnosed with Zinner syndrome. First, we performed transperineal puncture of the ureterocele because it closed the bladder neck during voiding. Although voiding symptoms temporarily improved, the ureterocele recurred soon and the urination disorder was reexacerbated. Next, we selected laparoscopic removal of the ureterocele and the seminal vesicle cyst. The procedure was performed with transperitoneal access using four trocars. Perioperative and postoperative complications were not observed, and micturition was satisfactory after surgery. Conclusion: Treatment for difficult urination because of Zinner syndrome is mostly selected puncture of the ureterocele or seminal vesicle cyst. However, some patients experience recurrence. The laparoscopic approach is minimally invasive and provides a satisfactory surgical field. Therefore, it should be considered the method of treatment for symptomatic Zinner syndrome.